Menara UEM Edgenta Berhad / Nurfarahanim Nazri ... [et al.] - Nurfarahanim, Nazri; Nur Hafizah, Youszelan; Izzmer Ahmad, Izzuddin; Mohd Mirwan Muzani, Mazni; Muhammad Yusri, Kamaruzaman (2019)
The building that we choose and decide for our case study is UEM Edgenta Berhad. UEM Edgenta Berhad is sited at Tower 1, Avenue 7, Jalan Kerinchi, Bangsar South, 59200 Kuala Lumpur, Wilayah Persekutuan Kuala Lumpur. This building is situated at Bangsar South City. Generally, this building is the medium rise building that was built at year 2012 and complete at year 2015 and operation at year 2015. So, this building now is around 5 years. This building is the office building. For the overall of our case study, this building not so much have the defects and had very good maintenance. It just take an action towards priority and also emergency. The services for the cleaning is very good and had very awesome landscape. For the maintenance budget is the main role for this building to ensure the building in a very good condition and had very good maintenance management. This building also have good services and maintained for the safety and health of occupants.